Flood-tolerant rice varieties for Bangladesh (sub1) - CGIAR Research Program on Rice (2018)
This study examines the adoption of submergence-tolerant (Sub1) rice varieties, grown in the Aman season in northwest Bangladesh, using data obtained from more than 1,100 farm households. The predicted probability of adopting Sub1 varieties is about 0.40, implying that 40% of the sampled farm households adopted Sub1 rice varieties.